A study on variations of foramen transversarium of cervical vertebrae - Magi Murugan; Suman Verma (Wolters Kluwer Medknow Publications, 2014)
Background and aims: Foramen transversarium of cervical vertebra is a bony enclosure for the vertebral artery. These foramina are known to exhibit variations in size, shape and may be multiple in number or absent. The aim of this study is to record these variations of foramen transversarium of cervical vertebrae. Material and methods: This study was carried out on 150 cervical vertebrae available in the department of anatomy at Pondicherry Institute of Medical Sciences. Results: Among 150 cervical vertebrae, 19 vertebrae were found to possess double foramina transversaria. Among these 15 were typical and four were atypical vertebrae. Among 15 typical cervical vertebra 12 (80%) had double foramina on right side, one (6.6%) on left side and two (13.3%) bilaterally. Among four atypical vertebra three (75%) possessed double foramina on right side and one (25%) bilaterally. In one typical vertebra there was an enmeshed foramen. Conclusions: The knowledge of these variations is important for radiologists in interpreting computed tomographs and magnetic resonance images.